The Conceptual Framework for Institutionalisation of E-court System in Pakistan - Qureshi, Zeeshan Ashraf; Nawaz, Hafiz Muhammad Usman; Baig, Mirza Shahid Rizwan (Journal of Peace, Development and Communication, 2021)
The paper is ensuring the efforts of Supreme Court of Pakistan to launch e-court system through video link connectivity for proceeding of cases through its different registries and, LHC and IHC have launched CMS and Mobile Applications for development of E-courts in Pakistan. The main objective of this research article is to propose a road map, how the existing ICT, E-courts can help Pakistani judiciary technology-driven approach with increased transparency. Moreover, how Pakistan can develop its model of E-courts to manage legal knowledge with integrity, quality and faster distribution of information, making the access to Justice easier and speeding up the whole judgement process. This research is based on a qualitative methodology to conduct a depth literature review and develop a conceptual model of E-courts through secondary data collected from libraries and internet sources. E-courts, working in different countries established through the utilization of the internet to ease the judicial proceedings for the litigant and all the other stakeholders in the process. The efforts specially targeted to help the poor. The E-courts has mainly provided a platform for the alliance of the ICT organization in the courts. In Pakistan E-courts model can be adequately adopted through computing machinery efficiently, more services, beyond as envisaged in the world for judicial proceedings must develop accordingly.